BS O01 Closure of mesenteric defects during laparoscopic roux-en-y gastric bypass surgery and its effect on internal hernia rates and small bowel obstruction: A Meta- Analysis. (7th December 2022) - Thomas, Rhys; Chalklin, Christopher; Carrington-Windo, Elliot; Beamish, Andrew; Barry, Jonathan
Abstract: Background: Roux-en-Y gastric bypass surgery is an important treatment for obesity and it's related diseases, however internal herniation and small bowel obstruction from mesenteric defects can lead to reoperation in 10–16% of patients. This can be early (<30 days) or late. Routine closure of meso-jejunal defecfs and/or Petersens defect is still not adopted worldwide. Our objective was to systematically review and analyse pooled data from all studies, evaluating the impact of routine closure of mesenteric defects on the incidence of internal hernia in laparoscopic antecolic Roux-en-Y gastric bypass (RYGB) surgery for obesity. Secondary endpoints for analysis included the incidence of early and late small bowel obstruction (SBO), need for reoperation, bleeding, anastomotic leak, marginal ulceration and weight loss. Methods: Ovid, MEDLINE, EMBASE and Cochrane databases were searched on 13 September 2021 using a combination of MeSH and non-MeSH terms, including 'gastric bypass', 'mesenteric defect', 'hernia', and 'small bowel obstruction'. Studies comparing closure with non-closure of mesenteric defects were included. Two researchers independently examined titles, then abstracts, and finally, full text articles. Disagreements were arbitrated with the senior author. Fixed- or random-effect models were used, as appropriate. Results have been reported with 95% confidence intervals and I-squared indices to assess uniformity among results for each outcome measured. Results: Seventeen studies met the criteria and were included, including two randomised trials. A total of 61, 220 patients were included with follow-up ranging from 24–120 months. In the closure group the incidence of all types of internal hernia was lower (OR 0.22, 95% CI 0.19, 0.26), SBO beyond 30 days was less frequent (OR 0.47, 95% CI 0.44, 0.52), and the reoperation rate was lower (OR 0.22, 95% CI 0.19, 0.26). The incidence of SBO within 30 days was higher in the closure group (OR 1.34, CI 1.07, 1.68). Conclusions: This new pooled analysis updates previous meta-analyses, adding data from eight additional studies and almost 45, 000 additional patients. This provides firm evidence that routine closure of mesenteric defects during laparoscopic gastric bypass reduces rates of internal herniation and SBO beyond the post-operative period. Closure of the mesenteric defects should be standard practice in RYGB. A higher incidence of early SBO was notable in the closure group, postulated by some studies as attributable to technical factors, including kinking of the jejunal anastomosis and bleeding. This must be considered when closing defects.